Prenatal exposure to antibiotics and risk of neurodevelopmental disorders in offspring: A systematic review and meta-analysis - Tao, Qiuji; Shen, Yajun; Li, Yang; Luo, Huan; Yuan, Meng; Gan, Jing (Frontiers in Neurology, 2022)
Background and Purpose: A growing body of research suggests that inflammation and maternal infections may lead to the increased risk of neurodevelopmental problems such as attention deficit hyperactivity disorder (ADHD), Autism Spectrum Disorder (ASD), cerebral palsy (CP), and epilepsy in offspring. The aim of this systematic review and meta-analysis is to look at the connection between the prenatal antibiotic exposure and the risk of these neurodevelopmental disorders in offspring. Patients and methods: A comprehensive search was conducted in CENTRAL (Cochrane Central Register of Controlled Trials), PubMed, Google Scholar and Scopus databases for observational studies that looked into the link between prenatal exposure to antibiotics and the risk of neurodevelopmental problems in offspring, published from January 01, 1950 to January 31, 2022. The Newcastle–Ottawa (NOS) scale was used to assess the quality of the included studies. Data was analysed using STATA version 12 software, and odds ratio (OR) with 95% confidence interval (CI) were reported. Results: Fifteen studies were included in the meta-analysis. Prenatal antibiotic exposure was associated with the increased risk of ADHD (OR=1.14; 95 % CI= 1.13 to 1.15, I2=0%) and epilepsy (OR=1.34; 95 % CI= 1.02 to 1.66, I2=96.8%). The link between prenatal antibiotic exposure and the risk of ASD [OR=1.09; 95 % CI= 0.88 to 1.31, I2=78.9%] and CP [OR=0.99; 95 % CI= 0.56 to 1.43, I2=91%] was found to be non-significant. In all of the included prospective cohort studies, subgroup analysis suggested a significant association between prenatal antibiotic exposure and the incidence of ASD [OR=1.17; 95% CI= 1.03 to 1.31, I2= 48.1%] and CP [OR=1.18; 95 percent CI= 1.02 to 1.34, I2=0%]. Conclusions: Prenatal antibiotic exposure during pregnancy is linked to a higher incidence of ADHD and epilepsy in the offspring. Further prospective studies that compare prenatal antibiotic use and are adjusted for various confounders are needed to further assess the association of prenatal antibiotic exposure and neurological disorders in offspring.